Capturing Employee Hearts: The Role of Leadership and Organizational Culture on Loyalty - Hosanna Agree R Manalu; Ratna Ida H Simanullang (Indonesian Development of Economics and Administration Journal, 2025)
This study aims to analyze the influence of leadership and organizational culture on employee loyalty in the banking and service sectors in South Jakarta. The focus is on how leadership style and organizational culture contribute to employees’ emotional attachment and commitment to the organization. Methodology/approach – A quantitative research approach was used, with data collected through questionnaires distributed to employees in the banking and service sectors. Multiple linear regression was employed to test the simultaneous and partial effects of leadership and organizational culture on employee loyalty. Findings – The study found that leadership significantly positively impacts employee loyalty, especially when leaders exhibit a participatory, communicative, and inspirational style. Additionally, a strong organizational culture characterized by shared values of togetherness, openness, and innovation also significantly strengthens employee loyalty. Novelty/value –  This research highlights the importance of combining effective leadership with a supportive organizational culture to foster long-term employee loyalty. The study provides valuable insights for organizations seeking to design strategies that enhance employee retention and commitment.